COVID-19 in children across three Asian cosmopolitan regions - Gilbert T. Chua; Xiaoli Xiong; Eun Hwa Choi; Mi Seon Han; Sung Hee Chang; Byoung Lo Jin; Eun Joo Lee; Baek Nam Kim; Min Kyoung Kim; Kihyun Doo; Ju Hee Seo; Yae Jean Kim; et al. (Emerging Microbes and Infections)
As another wave of COVID-19 outbreak has approached in July 2020, a larger scale COVID-19 pediatric Asian cohort summarizing the clinical observations is warranted. Children confirmed with COVID-19 infection from the Republic of Korea, the Hong Kong Special Administrative Region (HKSAR) and Wuhan, China, during their first waves of local outbreaks were included. Their clinical characteristics and the temporal sequences of the first waves of local paediatric outbreaks were compared. Four hundred and twenty three children with COVID-19 were analyzed. Wuhan had the earliest peak, followed by Korea and HKSAR. Compared with Korea and Wuhan, patients in HKSAR were significantly older (mean age: 12.9 vs. 10.8 vs. 6.6 years, p < 0.001, respectively) and had more imported cases (87.5% vs. 16.5% vs. 0%, p < 0.001, respectively). The imported cases were also older (13.4 vs. 7.6 years, p < 0.001). More cases in HKSAR were asymptomatic compared to Korea and Wuhan (45.5% vs. 22.0% vs. 20.9%, p < 0.001, respectively), and significantly more patients from Wuhan developed fever (40.6% vs. 29.7% vs. 21.6%, p=0.003, respectively). There were significantly less imported cases than domestic cases developing fever after adjusting for age and region of origin (p = 0.046). 5.4% to 10.8% of patients reported anosmia and ageusia. None developed pediatric multisystem inflammatory syndrome temporally associated with SARS-CoV-2 (PMIS-TS). In general, adolescents were more likely to be asymptomatic and less likely to develop fever, but required longer hospital stays. In conclusion, majority patients in this pediatric Asian cohort had a mild disease. None developed PIMS-TS. Their clinical characteristics were influenced by travel history and age.